2021
DOI: 10.3390/pharmaceutics13122041
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lipid-Based Nanocarriers for Antitubercular Drug Delivery: A Review

Abstract: The antimicrobial drugs currently used for the management of tuberculosis (TB) exhibit poor bioavailability that necessitates prolonged treatment regimens and high dosing frequency to achieve optimal therapeutic outcomes. In addition, these agents cause severe adverse effects, as well as having detrimental interactions with other drugs used in the treatment of comorbid conditions such as HIV/AIDS. The challenges associated with the current TB regimens contribute to low levels of patient adherence and, conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 125 publications
(163 reference statements)
0
27
0
2
Order By: Relevance
“…The main issue is poor stability compared to other drug carriers (Roohinejad et al 2018 ; Thorn et al 2021 ). Traditional liposomes greater than 100 nm are rapidly cleared from blood circulation by circulating macrophages or dendritic cells as part of the reticuloendothelial system (Buya et al 2021 ; Anali Bazán Henostroza et al 2022 ). Hydrophilic polymers such as polyethylene glycol, pectin or chitosan can protectively coat the surface of liposomes, increasing their residence time in the blood circulation (Anabousi et al 2006 ; Icriverzi et al 2019 ; Buya et al 2021 ).…”
Section: Liposomesmentioning
confidence: 99%
See 3 more Smart Citations
“…The main issue is poor stability compared to other drug carriers (Roohinejad et al 2018 ; Thorn et al 2021 ). Traditional liposomes greater than 100 nm are rapidly cleared from blood circulation by circulating macrophages or dendritic cells as part of the reticuloendothelial system (Buya et al 2021 ; Anali Bazán Henostroza et al 2022 ). Hydrophilic polymers such as polyethylene glycol, pectin or chitosan can protectively coat the surface of liposomes, increasing their residence time in the blood circulation (Anabousi et al 2006 ; Icriverzi et al 2019 ; Buya et al 2021 ).…”
Section: Liposomesmentioning
confidence: 99%
“…Traditional liposomes greater than 100 nm are rapidly cleared from blood circulation by circulating macrophages or dendritic cells as part of the reticuloendothelial system (Buya et al 2021 ; Anali Bazán Henostroza et al 2022 ). Hydrophilic polymers such as polyethylene glycol, pectin or chitosan can protectively coat the surface of liposomes, increasing their residence time in the blood circulation (Anabousi et al 2006 ; Icriverzi et al 2019 ; Buya et al 2021 ). It has also been shown that liposomes prepared from milk derived phospholipids or rapeseed oil can slow the digestion of LF in simulated gastric and intestinal conditions (Liu et al 2013 ; Vergara et al 2020 ).…”
Section: Liposomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipid-based emulsion systems, including microemulsion, nanoemulsion, niosomes, SMEDDS (self microemulsifying drug delivery systems), and SNEDDS (self-nanoemulsifying drug delivery systems), have been proven to promote solubility and bioavailability, highlighting the potential value of this type of delivery approach for water-insoluble bioactive molecules [ 18 , 19 , 20 ]. Furthermore, encapsulating drugs in emulsion can also protect it from degeneration, control the release, and minimize the side effects [ 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%